MEASURED BEHAVIOR OF A TRIAL EMBANKMENT ON FLOATING COLUMN IMPROVED SOFT ARIAKE CLAY DEPOSIT - Y. Igaya; T. Hino; J.-C. Chai (Lowland Technology International, 2011)
A 6.5m height trial embankment was constructed on soft Ariake clay deposit improved by the floating soil-cement columns. At the test site, the thickness of the soft soil was about 10 m, and the length of the column was 8.5 m and the area improvement ratio was about 31%. To check both the mechanical and geoenvironmental performance, the embankment was monitored for more than 2 years. The measured results indicate that the behavior of the trial embankment satisfies the performance requirements for constructing a highway around Ariake Sea, in Kyushu, Japan, i.e. settlement and lateral displacement at the toe of the embankment are less than 50 mm, and residual settlement is less than 0.3 m. The observed results also show that the column improvement not only reduced the settlement but also accelerated the consolidation rate of the deposit. The results of groundwater monitoring indicate that at the test site, in terms of groundwater level, flow velocity, pH value and the concentrations of some key ions, there was no effect on the groundwater quality due to the installation of soil-cement columns into the ground.